Communication Models in Contemporary Art - Navickaitė, Rugilė (Vilnius University Open Series, 2021)
The object of research is the communication features of contemporary art. The aim is to reveal these features based on a review of the literature. The paper discusses the concept of communication in contemporary art; describes the characteristics of contemporary art as a medium; defines communication models in contemporary art. Communication and its features are manifested in many fields, one of which is art. To discuss the concept of communication in contemporary art, the levels of verbal and nonverbal communication are distinguished. Image forms, colours, lighting, lines, motifs, body language, sound, as well as the written or unwritten language of verbal communication about a work of art, can serve to recognise the communicative properties of a work of art. Types of intrapersonal and public and mass communication are applied, communication process models are based.
Keywords: communication; contemporary art; participation; spectator